Vous êtes sur la page 1sur 12

# M ( 1 )

5x + 1 x + 1 2x + 1
:
<
+
6
2
3
1 : ... ( ).
5x + 1
x +1
2x + 1
5x + 1 < 3.(x + 1) + 2.(2x + 1)
6.
< 6.
+ 6.
3
6
2
2 : ( ).
5x + 1 < 3x + 3 + 4x + 2
3 : X ( ).
5x - 3x - 4x < 3 + 2 - 1
4 : .
- 2x < 4
5 : ( ).
" - ", .
-2x 4

> -2
>
x
-2 H -
2
:
0.x > , "" > 0, " x" < 0.
0.x < , "" < 0, " x" > 0.

: http://drmaths58.blogspot.com/

1
3. 2 + 110 20. ;
: x + > 0 ,
2. A , , = 3 + 3 , = 2 + 2 .
> 0 : x >

< 0 : x <
= 0 > 0 x
= 0 < 0
= 0 = 0
: x + < 0 ,

> 0 : x <

< 0 : x >
= 0 > 0
= 0 < 0 x
= 0 = 0

## 1. 0.x > > 0 x < 0.

2. 0.x < x > 0 < 0.
3. 0.x > 0
4. 0.x < 0

M ( )
: 2 (x - 1) x - 3 + 2 .
1 : M , .x > < B, , .
2 (x - 1) x - 3 + 2 2x - 2 x - 3 + 2 2x - x 2 - 3 + 2
( 2 - 1)x 2 - 3 + 2 ( + 1)( - 1)x ( - 1)( - 2) ()

, : x > <

B
( ).
A

-2
+1
4 : .
( + 1)( - 1) = 0, = 1 = -1, :
= 1 () :
( + 1)( - 1) < 0, - 1 < < 1, () : x

## 0.x (1 - 1)(1 - 2) 0.x 0.(-1) 0.x 0, x.

= -1 () :
0.x (-1 - 1)(1 - 2) 0.x (-2).(-1) 0.x 2, .

M ( )
| x-1 | | 1-x |
:
+
<| -2x + 2 | -7
3
2
1 : , ( ).
| x -1| |x -1|

+
< 2. | x - 1 | -7
3
2
2 : 1 .
| x -1|
|x -1|
6.
+ 6.
< 6.2. | x - 1 | -6.7 2. | x - 1 | +3. | x - 1 |< 12. | x - 1 | - 42
3
2
2. | x - 1 | +3. | x - 1 | -12. | x - 1 | < - 42 -7. | x - 1 | < - 42 | x - 1 | < 6
3 : :

. | f(x) |< , :

< 0 .
.

>
0

:
f(x)
<
-

f(x)
>
.

. | f(x) |> , :

< 0 x.

## - 6 < x - 1 < 6 -6 + 1 < x - 1 + 1 < 6 + 1 -5 < x < 7.

: http://drmaths58.blogspot.com/

2 : ,
B
, : x > < ( ).
A
-2
( + 1)( - 1) > 0, < -1 > 1, () : x
+1
3 : , -

M ( )
:| x - 1 | + | 2x - 4 |< 1
1 :
, .
|x-1| x=1
|2x-4| x=2

|x-1|

-x-1

x+1

x+1

|2x-4|

-2x-4

-2x-4

2x+4

2 :

4
, x < 1.
3
1 x < 2, :

4
.
3

: x < 1 x <

## x - 1 - 2x + 4 < 1 x - 2x < 1 + 1 - 4 -x < - 2 x < 2 .

: 1 x < 2 x < 2, 1 x < 2.
x 2, :
x - 1 + 2x - 4 < 1 x + 2x < 1 + 1 + 4 3x < 6 x < 2 ( ).
: (-, 1)U[1, 2) = (-, 2) x < 2.

: http://drmaths58.blogspot.com/

.
x < 1, :

x+3 x+1
3+x

2
4
3

x+2 x
1
4
3

x x+1
<0
5
15

E
x + 3 x + 1 3 - x =12
x +3
x +1
3+x

12.
- 12.
12.
6(x + 3) - 3(x + 1) 4(3 + x)
2
4
3
2
4
3
6x + 18 - 3x - 3 12 + 4 6x - 3x - 4x 12 - 18 + 3 -x -3 x 3

:
| x - 1 |< 6
| x - 2 | 0
| x - 5 | > -1

| x - 3 |< -3
| x -4 | 2
| x -4 | | 4-x |
| 2x - 8 |

| x - 6 | >| x - 7 |
+
3
2
4
(+1)

## | x - 1 |< 6 -6 < x - 1 < 6 - 6 + 1 < x - 1 + 1 < 6 + 1 -5 < x < 7

| x - 2 | 0 x - 2 = 0 x = 2
| x - 4 |< -3 - 3 < 0 | x - 4 |> 0
| x - 4 | 2 (x - 4 2 x - 4 -2) x 6 x 2
| x - 5 | > -1 x - 1 < 0 | x - 5 |> 0
| x - 6 | >| x - 7 | | x - 6 |2 >| x - 7 |2 (x - 6)2 > (x - 7)2
13
x2 - 12x + 36 > x2 - 14x + 49 2x > 13 x >
2
| x - 4 | | 4 - x | | 2x - 8 | | x - 4 | | -(x - 4) | | 2(x - 4) | ||=|-|

3
2
4
3
2
4
|x - 4| |x - 4|
|x - 4|
|x - 4|
|x - 4|
|x-4|
+
2
6.
+ 6.
6.

3
2
4
3
2
2
2 | x - 4 | +3 | x - 4 | 3 | x - 4 | 2 | x - 4 | 0 x - 4 = 0 x = 4

: http://drmaths58.blogspot.com/

x +2
x
x + 2 x

4 - 3 1
12. 4 - 12. 3 12
3(x + 2) - 4x 12
3x + 6 - 4x 12

3x - (x + 1) < 0
3x - x - 1 < 0
x - x + 1 < 0
15. x - 15. x + 1 < 0
15
5
15
5

x -6
-x 6
1

1 -6 x <
2
2x < 1
x < 2

:
(x - ) < 3(x - 3)

## (x - ) < 3(x - 3) x - 2 < 3x - 9 x - 3x < 2 - 9 ( - 3)x < ( + 3)( - 3)

- 3 > 0, > 3, () , : x >

()

( + 3)( - 3 )
x > + 3
-3

( + 3)( - 3 )
x < +3
-3
- 3 = 0, = 3 , () : 0.x < (3 + 1)(3 - 3) 0.x < 0,
- 3 < 0, < 3, () , : x <

x . , :
32

x<

2x + x < 32
3x < 32
55
32

3
<x<

6
3
5x + x > 55
6x > 55
x > 55

6
32
55

, x = 10.
O,
6
3

x +

x +

x
x

< 16
2.x + 2. < 2.16

2
2

x
x

> 11
5.x + 5. > 5.11

5
5

1 | x + 3 |< 5

| 3- | 2x - 4 || 6

x + 3 -1
x -4

| x + 3 | 1

1 | x + 3 |< 5

x (-8, -4]U[-2, 2).
x
+
3
1
x
-2

| x + 3 |< 5

-5 < x + 3 < 5
-8 < x < 2

| 3- | 2x - 4 || 6 -6 3- | 2x - 4 | 6 -9 - | 2x - 4 | 3 -3 | 2x - 4 | 9

1
x 2
2x - 4 -3

| 2x - 4 | -3
5 1
7 13

x [- , ]U[ , ].
7

2 2
2 2
| 2x - 4 | 9
2x - 4 3
x 2

-9 < 2x - 4 9

13
5
- 2 x 2

: http://drmaths58.blogspot.com/

, :
16.
1

11.
5

:
3 | x - 1 | - | x - 2 |< 3x
x = 1 x = 2. : (-, 1), [1, 2) [2, +).
: (-, 1) : | x - 1 |= -x + 1, | x - 2 |= -x + 2 :
3(-x + 1) - (-x + 2) < 3x -3x + 3 + x - 2 < 3x -5x + 1 < 0 x < 1
.
5

: [1, 2) : | x - 1 |= x - 1, | x - 2 |= -x + 2 :
3(x - 1) - (-x + 2) < 3x 3x - 3 + x - 2 < 3x x < 5,
1 x < 2.
: [2, +) : | x - 1 |= x - 1, | x - 2 |= x - 2 :
3(x - 1) - (x - 2) < 3x 3x - 3 - x + 2 < 3x -x < 1 x > -1,
x 2.
1
A x (-, - )U[1, +).
5

: http://drmaths58.blogspot.com/

x < -

1
,
5

:
5x + 6 x
2x - 1

- 4
8
3
9
x + 10 2x - 7

>
+4
9
3
:
x -1 x +1 x
x +1 x +2 x

3
2
6
4
8
8
x + 1 2x + 1

## 2(x2 - 1) + 5 > x(2x - 1) + 4x

2
5

x - 1 x + x

+
>
,
2
12
6
4(x - 1)2 - (x - )2 > 3(x + )2 - 2 2 ,
H .
19 7 .
.
49 ,
, , 106 .

: .x > B
(I)
<

( ).
x .
, .

.

( );
,

x .
' , .
3.

.

:
25.

.
, :
.
.
76.
70.

x .
, .

.

: http://drmaths58.blogspot.com/

,
.

, .

AYT
:
| x + 3 |< 3
| 2x - 4 | 0
| 3x + 2 |< 0
| 4x - 8 | 2
| 5x - 1 | > -1
| x + 1 | >| x - 2 |

2 | 3x - 2 | +4 6- | 3x - 2 | | 2 - 3x |
>
-2
4
2
3

- 1 | x - 2 |< 3
| 1- | x - 3 || 5

:
| x + 1 | - | x - 2 | 1
| x + 1 | - | 2x - 4 | 1
2 | x - 1 | +3 | x + 2 | < 0
| 2- | x + 1 || < 3

:
| x |< , > 0 :
- < x <
| x |> , > 0 :
x > x < -
B x

' ...

: http://drmaths58.blogspot.com/

:
| x |< , > 0 :
- < x <
| x |> , > 0 :
x >

x < -

2
x +x + = x +
= (x - x0) .
2

< 0 x+x+ 0 :
2

| |
x + x + = x +
+
.
2
4 2

> 0 x+x+ 0 x1 < x2:
, x1 < x < x2
, x < x1 x > x2
= 0 x+x+ 0
< 0 x+x+ 0
:
(x)
B(x)
(x)

B(x)
(x)

B(x)
(x)

B(x)

## > 0 : : A(x).B(x) > 0

0 : : A(x).B(x) 0
< 0 : : A(x).B(x) < 0
0 : : A(x).B(x) 0

: :

(x)
< > (x)
B(x)

. , .

: http://drmaths58.blogspot.com/

, :
f(x) = x + x + ,, 0.
T, : x + x + 0.
: x+x+=0

> 0 x+x+ 0 ,
x1, x2 : x + x + = (x - x1)(x - x2) .
-
= 0 x+x+ 0 , x0 =
:
2

10

:
(x - 1)(x 2 - 2x + 5)(-x 2 + 5x - 6) 0
x < 1 x - 1 < 0
x - 1 = 0 x = 1,
x > 1 x - 1 > 0
x2 - 2x + 5 = 0 = (-2)2 - 4.1.5 = 4 - 20 = -16 < 0 x 2- 2x + 5 > 0 x .

x-1
x2-2x+5

-x +5x-6

(x)

: [1, 2]U[3,+ ) .

(x + 2)(x 2 + 6x + 9)
0
x 2 - 5x + 6

x < -2 x + 2 < 0
x + 2 = 0 x = -2,
x > -2 x + 2 > 0
x2 + 6x + 9 = 0 (x + 3)2 = 0 x = -3 = 62 - 4.1.9 = 36 - 36 = 0,
x 2+ 6x + 9 > 0 x .

5 +1

= 1
x=

x = 3

x2 - 5x + 6 = 0
51
5
1
x
=
2
x
=

x =
2

2
H :

## x2 - 5x + 6 > 0 x < 2 x > 3

2
x - 5x + 6 < 0 2 < x < 3

(x + 2)(x2 + 6x + 9)(x2 - 5x + 6) 0, x 2 x 3.
:
x

-3

-2

x+2

x2+6x+9

x2-5x+6

(x)

## A : [-2, 2)U(3, +).

: http://drmaths58.blogspot.com/

-5 + 1

= 1
x=

## x = 2 -x2 + 5x - 6 > 0 2 < x < 3

-2
2
- x + 5x - 6 = 0 :

2
-5 1
x = 3 -x + 5x - 6 < 0 x < 2 x > 3
x = -2
x = -5 - 1

-2
:

11

:
x - 1 > 0
2
x - 2x + 5 > 0
-x 2 + 5x - 6 0

x < 1 x - 1 < 0
x - 1 = 0 x = 1,
x > 1 x - 1 > 0
2
x - 2x + 5 = 0 = (-2)2 - 4.1.5 = 4 - 20 = -16 < 0,
x 2- 2x + 5 > 0 x .

x-1

x2-2x+5

-x2+5x-6

A : [2, 3].

: http://drmaths58.blogspot.com/

-5 + 1

= 25 - 24 = 1
x=

x = 2

-2
- x2 + 5x - 6 = 0

-5 1
x = 3
x = -2
x = -5 - 1

-2
2
-x + 5x - 6 > 0 2 < x < 3
o 2
-x + 5x - 6 < 0 x < 2 x > 3
:

12

:
(x - 2)(x + 2x - 8)(x + x + 1) > 0
2

## (2x - 1)(-x2 + 2x - 1)(x2 + 1) > 0

(x - 3)(x2 + 3x - 10)(-x2 + x - 10)(x2 - 4) 0
(x - 2)(x2 - 7x + 6)(-x2 - 2x + 8)(x2 - 1) > 0

(x - 1)(x - x + 1)
0
-x2 + x + 6
10
x+2
x-3
2
+
<
x - x - 6 x - 3 x + 2x

:
x2 - 3x + 2 > 0

(1 ) : x2 - 5x - 50 < 0
x2 - 2x - 15 > 0

x - 2 > 0

(2 ) : 6x2 + 5x + 1 > 0
-x2 + 5x - 6 0

x-2
>0

(3 ) : 2x + 1
(x2 - 4)(x2 + 2x + 4 > 0

f(x) = x 2 + x + ,
x1 x2 , x1 < x2
:
= 0
< 0 > 0 x < x1 x > x2
> 0
x1 < x < x 2

f(x) = x 2 + x + ,
x1 x2 , x1 < x2
:
= 0
< 0 > 0 x < x1 x > x2
> 0
x1 < x < x 2

: http://drmaths58.blogspot.com/

f(x) = x 2 + x + ,
x1 x2 , x1 < x2
:
= 0
< 0 > 0 x < x1 x > x2
> 0
x1 < x < x 2